First-principles calculations of the water molecules and hydroxylated iron surface. Issue 175 (12th October 2016) - Nunomura, Norio; Sunada, Satoshi
ABSTRACT: To provide atomic scale understanding of the initial corrosion process of Fe in aqueous environment, the electronic interaction of between water molecules and hydroxyl groups with the (110) and (100) surface of Fe is investigated in a density functional theory approach. Using periodic slab models, stable structures and electronic states are calculated, and the dynamical behavior of water molecules and hydroxylated iron surface under finite temperature is resolved by first-principles molecular dynamics. The position of hydroxyl groups on surface does not change from the initial bridge position, while water molecules move from the initial on-top to bridge site, and the molecular surface tilts from a parallel position, the hydrogen bonds are also formed between water molecules and hydroxyl groups. This result suggests that the interaction due to the hydrogen bonding is dominant.